2021
DOI: 10.2196/25762
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of the Effectiveness of Identity-Based Public Health Announcements in Increasing the Likelihood of Complying With COVID-19 Guidelines: Randomized Controlled Cross-sectional Web-Based Study

Abstract: Background Public health campaigns aimed at curbing the spread of COVID-19 are important in reducing disease transmission, but traditional information-based campaigns have received unexpectedly extreme backlash. Objective This study aimed to investigate whether customizing of public service announcements (PSAs) providing health guidelines to match individuals’ identities increases their compliance. Methods W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Wei, 2023a). Relevant research shows that tailored messages contribute to improving trust and public health uptake (Dennis et al, 2021;Murthy et al, 2020;Ontario Agency for Health Protection and Promotion, 2023;Slavik et al, 2021) and that messages in risk communication should be transparent, evidence-based and action-oriented (Ontario Agency for Health Protection and Promotion, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Wei, 2023a). Relevant research shows that tailored messages contribute to improving trust and public health uptake (Dennis et al, 2021;Murthy et al, 2020;Ontario Agency for Health Protection and Promotion, 2023;Slavik et al, 2021) and that messages in risk communication should be transparent, evidence-based and action-oriented (Ontario Agency for Health Protection and Promotion, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In most circumstances, a public service announcement (PSA) on public health and safety issues is regarded to be one of the most successful ways to influence behaviour change (İnci1, Sancar & Bostancı, 2017). For example, Dennis et al (2021) in their study discovered that public service announcements (PSA) carrying Covid-19 messages that are customised to individuals' identities have a high potential to increase compliance with public health guidelines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PSAs are government or non-government sponsored messages that are meant to inform and persuade individuals to adopt desirable behaviors that benefit themselves and society [29]. Early research on COVID-19 has shown PSAs to be effective in combating hesitancy and promoting vaccinations [30] and wearing masks [31]. PSAs may help mitigate high levels of uncertainty and anxiety associated with the pandemic.…”
Section: Introductionmentioning
confidence: 99%